Pengaruh Remunerasi dan Motivasi Kerja terhadap Kinerja Karyawan PT Naturalva Herba Indonesia - Vicko Anggara Putra; Ahmad Gunawan (JUDICIOUS, 2023)
PT Naturalva Herba Indonesia is a startup nutrition company engaged in the production & distribution of herbal nutrition which was established in February 2021. Products made specifically to treat symptoms of acid reflux (Gerd) with the brand Gerd Zero Pro. This research was conducted to determine the effect of remuneration and work motivation variables on the performance of employees working at PT Naturalva Herba Indonesia with a total of 41 employees. The type of research used is to use quantitative methods through population calculations and samples using questionnaires to 41 employees of PT Naturalva Herba Indonesia whose validity and reliability have been tested using IBM SPSS 25 software. Based on the overall results of the tests that have been carried out with the software, it is found that the Remuneration and Work Motivation variables together have a significant effect on employee performance at PT Naturalva Herba Indonesia. This is in accordance with the results of the research hypothesis, namely in the partial test (t test) the value of t count is more than the value of t table and the significance value is less than the significance level.